IBEXSec:a universal security framework for industrial internet terminal access - Yuan CHEN; Tieming CHEN; Qijie SONG; Dongjie MA (Dianxin kexue)
s:With the development and application of the industrial internet platform,the security risks of massive heterogeneous terminals need to be solved urgently.Aiming at the current industrial internet terminal access and data transmission security problems,a universal terminal security service framework called IBEXSec based on the identity public key cryptographic service (IBE-XKMS) was proposed to support security functions such as secure access,authentication agents,cross-domain communications and privacy protection of heterogeneous terminal devices on the industrial internet.